1998
DOI: 10.1086/305621
|View full text |Cite
|
Sign up to set email alerts
|

Hubble Space TelescopeImaging of the CFRS and LDSS Redshift Surveys. I. Morphological Properties

Abstract: We analyse Hubble Space Telescope images of a complete sample of 341 galaxies drawn from both the Canada France and Autofib/Low Dispersion Survey Spectrograph ground-based redshift surveys. In this, the first paper in the series, each galaxy has been morphologically classified according to a scheme similar to that developed for the Medium Deep Survey. We discuss the reproducibility of these classifications and quantify possible biases that may arise from various redshift-dependent effects. We then discuss auto… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

29
277
3

Year Published

2000
2000
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 209 publications
(309 citation statements)
references
References 36 publications
(48 reference statements)
29
277
3
Order By: Relevance
“…11). In contrast, none of our Groth Strip QS-E/S0's are classified as non-E/S0's by Brinchmann et al (1998). Thus, we conclude that our method is somewhat more conservative than the AC method in picking up only morphologically featureless E/S0's.…”
Section: No 1 2002mentioning
confidence: 68%
See 3 more Smart Citations
“…11). In contrast, none of our Groth Strip QS-E/S0's are classified as non-E/S0's by Brinchmann et al (1998). Thus, we conclude that our method is somewhat more conservative than the AC method in picking up only morphologically featureless E/S0's.…”
Section: No 1 2002mentioning
confidence: 68%
“…E/S0's in Im et al (1999) are selected as galaxies that have a significant bulge (B=Te0:3) and appear morphologically featureless when visually classified. They present redshift distributions of various galaxy types and find that that of E/S0's is consistent with no number density evolution out to z $ 1 (for similar works, see Roche et al 1998;Driver et al 1998;Brinchmann et al 1998). However, the number of early-type galaxies in both of these studies is small (about 40), and thus it is difficult to draw firm conclusions.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…A large sample of faint galaxies with spectroscopic redshift is quite difficult to obtain at high redshift, but is necessary to properly estimate the environment. Intermediate depth surveys with HST combined with ground based spectroscopy have shown that the Hubble sequence is in place at z ∼ 1 (e.g., Lilly et al 1995;Abraham et al 1996;Brinchmann et al 1998;Abraham et al 2007). Likewise, deep observations at high resolution were difficult to achieve before the advent of the Hubble Space Telescope (HST) Advanced Camera for Survey (ACS).…”
Section: Introductionmentioning
confidence: 99%